2017
DOI: 10.1103/physrevlett.119.235701
|View full text |Cite
|
Sign up to set email alerts
|

Melting Curve and Liquid Structure of Nitrogen Probed by X-ray Diffraction to 120 GPa

Abstract: Synchrotron x-ray diffraction measurements of nitrogen are performed up to 120 GPa to determine the melting curve and the structural changes of the solid and liquid phases along it. The melting temperature exhibits a monotonic increase up to the triple point where the epsilon molecular solid, the cubic gauche covalent solid, and the fluid meet at 116 GPa, 2080 K. Above, the stability of the cubic gauche phase induces a sharp increase of the melting curve. The structural data on liquid nitrogen show that the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…In dense monatomic liquids it is empirically found that the position of the maximum of the FDP, Q M is related to the density ρ through the relation Q M 4.4(4πρ/3) 1/3 [63], and thus (Q M /Q M 0 ) 3 ρ/ρ 0 where Q M 0 and ρ 0 correspond to a reference state. This relation has also been found to be verified in molecular liquids with weak orientational correlations, such as H 2 [26] and N 2 [28]. To test whether it also holds in ammonia, we plot in Fig.…”
Section: A Experimentssupporting
confidence: 56%
See 1 more Smart Citation
“…In dense monatomic liquids it is empirically found that the position of the maximum of the FDP, Q M is related to the density ρ through the relation Q M 4.4(4πρ/3) 1/3 [63], and thus (Q M /Q M 0 ) 3 ρ/ρ 0 where Q M 0 and ρ 0 correspond to a reference state. This relation has also been found to be verified in molecular liquids with weak orientational correlations, such as H 2 [26] and N 2 [28]. To test whether it also holds in ammonia, we plot in Fig.…”
Section: A Experimentssupporting
confidence: 56%
“…The purpose of the present study is to extend the experimental investigation to higher pressures in order to determine the structural evolution over a larger range of densities. To this end, we used recently developed techniques for the measurement of the structure of low-Z fluids in the diamond anvil cell by synchrotron x-ray diffraction [25], which have been successfully used in the recent past to study liquid hydrogen [26] and carbon dioxide [27] and allowed to determine the melting lines of liquid nitrogen [28] and ammonia [29] up to the megabar range. Here we present experimental data for liquid ammonia obtained at 690 K and 800 K up to 6.3 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Assigning peak positions to a specific temperature would require the knowledge of the temperature distribution inside the sample, which is not trivial and beyond the scope of this study. Similarly we could not extract the structure factor of the liquid phase as in our previous work on nitrogen 39 due to the weak liquid diffuse scattering signal and poor signal-to-noise ratio.…”
Section: A X-ray Diffraction Experimentsmentioning
confidence: 91%
“…A 1-2 μm thick Al 2 O 3 or LiF layer was coated on the pitted anvil culets for thermal insulation. This geometry is similar to the one used for the determination of the nitrogen melting curve [21] and provides uniform heating of the sample.…”
Section: Methodsmentioning
confidence: 99%